Handlungsempfehlung zur prähospitalen Notfallnarkose beim Erwachsenen: Arbeitsgruppe „Prähospitale Notfallnarkose“ des Wissenschaftlichen Arbeitskreises Notfallmedizin der Deutschen Gesellschaft für Anästhesiologie und Intensivmedizin = Practice management guideline on prehospital emergency anaesthesia : working group “Prehospital emergency anaesthesia” of the scientific working group on emergency medicine of the German Society of Anaesthesiology and Intensive Care Medicine - Bernhard, Michael; Popp, Erik (Notfall & Rettungsmedizin, 2015)
Inducing anaesthesia outside the hospital is an important therapeutic intervention in emergency medicine; it is much more difficult to accomplish than inside the hospital. Its primary goals include hypnosis and analgesia which enable airway management to achieve mechanical ventilation and adequate oxygenation. Secondary goals of emergency anaesthesia include amnesia, anxiolysis, reduced oxygen consumption and work of breathing, and thus protection of vital organs and avoidance of secondary myocardial injury or cerebral injuries. Prior to prehospital induction of anaesthesia, patient-, scene- and operator-specific factors need to be considered. The rapid sequence induction includes basic monitoring, pre-oxygenation, standardized preparation of drugs and equipment, administration of drugs, removal of the cervical collar and manual in-line stabilization during intubation attempt (if needed), intubation and confirmation of endotracheal intubation. Every spontaneously breathing emergency patient should receive pre-oxygenation for at least 3-4 min with 12-15 l oxygen per min and a tight-sealing facemask, or a demand valve. The standardized preparation process includes preparation and labeling drugs/syringes, checking the bag-valve mask, preparing the endotracheal tube with a stylet and blocking syringe, as well as having a stethoscope and material to secure the tube at hand, as well as alternative airway devices. It also includes immediate access to alternative means of airway management, as well as a suction unit, ventilator and monitoring devices including capnography. Basic monitoring for prehospital emergency anaesthesia includes ECG, an automatic/manual blood pressure cuff, and pulse oximetry. Continuous capnography is used without exception to confirm ventilation, to detect possible disconnections/dislocations, and for indirect monitoring of hemodynamics. Prior to induction of prehospital emergency anaesthesia, two peripheral intravenous catheters should be placed if possible.